2005
DOI: 10.1080/00420980500185462
|View full text |Cite
|
Sign up to set email alerts
|

Extent, Location and Profiles of Continuing Gentrification in Canadian Metropolitan Areas, 1981-2001

Abstract: This study looks at the changes in 10 Canadian CMAs between 1981 and 2001 and builds on the work of other Canadian researchers to show how the extent, location and nature of gentrification processes have continued since the 1970s. The analysis of census data from 1981 and 2001 identifies gentrifying tracts and compares them with the neighbourhoods that are recognised by local housing market analysts as gentrifying and with the neighbourhoods that are clearly not gentrifying. Gentrification between 1981 and 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 31 publications
2
55
0
Order By: Relevance
“…Whereas ageing may have brought newer buildings down in price in the past to yield the steeper 1981 profiles, the changes since 1981 have made the older buildings relatively more expensive. This finding supports the view presented by Meligrana and Skaburskis (2005) that gentrification pressures are widespread and affect much larger portions of the older parts of the city than is apparent by just looking at the physical changes to the neighbourhoods. The changes in the income profiles in Toronto and Vancouver support this conclusion.…”
Section: The Changing Profilessupporting
confidence: 90%
“…Whereas ageing may have brought newer buildings down in price in the past to yield the steeper 1981 profiles, the changes since 1981 have made the older buildings relatively more expensive. This finding supports the view presented by Meligrana and Skaburskis (2005) that gentrification pressures are widespread and affect much larger portions of the older parts of the city than is apparent by just looking at the physical changes to the neighbourhoods. The changes in the income profiles in Toronto and Vancouver support this conclusion.…”
Section: The Changing Profilessupporting
confidence: 90%
“…There are two major studies that use aggregate statistics to determine the extent and location of gentrification across cities in Canada (Meligrana & Skaburskis, 2005;Walks & Maaranen, 2008). The Walks and Maaranen (2008) study, which builds upon Hammel and Wyly (1996), Wyly and Hammel (1998), Meligrana and Skaburskis (2005), and Heidkamp and Lucas (2006), detects gentrification across Montreal, Toronto, and Vancouver using principal component analysis (PCA).…”
Section: Urban Geographymentioning
confidence: 99%
“…The Walks and Maaranen (2008) study, which builds upon Hammel and Wyly (1996), Wyly and Hammel (1998), Meligrana and Skaburskis (2005), and Heidkamp and Lucas (2006), detects gentrification across Montreal, Toronto, and Vancouver using principal component analysis (PCA). They uncover a classification of neighborhood gentrification and upgrading occurring in stages within the 1971-2001 period using census tract data.…”
Section: Urban Geographymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the economic reality encourages young adults to move into inner city neighborhoods because of the possibility of staying in smaller housing units at a lower total cost, compared to buying a single-family housing unit in suburbs. In the case of more desirable urban locations with higher rents, young people can trade off potentially higher housing costs for walkable and lifestyle amenities, as well as lower transportation costs [63,64,66]. In this context, a recent study conducted by Moos (2015) showed that gentrified areas are more likely to be occupied by young age residents.…”
Section: Walkable Neighborhood Amenitiesmentioning
confidence: 99%